Embodied Active Tactile Perception - He, Liang; Maiolino, Perla (IOP conference series. Materials Science and Engineering, 2023)
Tactile perception plays an important role in an agent safely interacting with the environment while acquiring information about it. Bio-inspired robotics opens up possibilities for a new paradigm leveraging the morphology of the body, which filters the tactile information in physical interactions and enables investigations of new designs for embodied active tactile perception. The subjects of morphology embodied active perception and motor embodied active perception is defined and discussed in this chapter. In the scope of morphology embodied active perception, sensor optimization and sensor adaptation are further defined to describe the change of sensor morphology in the design phase and the interacting phase, respectively. More specifically, the concept of online and offline sensor adjustment is presented. Sensor optimization is solely considered in the offline process for optimization and evolution design of the sensor structure and characteristics. Sensor adaptation and motor embodied active perception are considered in the online process to actively shape the sensing process with the morphology change of the sensors themselves and the action of the body where the sensors are placed, respectively. “Design as a whole” is proposed as an inverse problem to address the sensing tasks. The design of new tactile sensors should not focus on the sensor per se but should also include design parameters for sensor optimization, sensor adaptation, and motor actions.